Development of milling ancilliary compatible with two-stroke power saw engine for short log conversion. (2010)
Chainsaw milling is an inevitable means of preventing quantum wastage of valuable and scarce wood resourse in un-accessible locations. Milling attachment (MA) was developed for a two stroke power chainsaw to reduce milling difficulties, risk and wastage. Operators of power-saw (90) were randomly selected and interviewed to elicit information on profile and limitations of chainsaw milling. Milling ancillary was developed for two stroke power-saw engine (T-S-PSE) with power to weight ratio rating and guide bar length of 1.5g/w and 75.0cm respectively. Results showed that only 33.3% had formal training while 65.6% were hitherto either unskilled labourers involved in logging activities or sawmill sawyers. About 57.8% respondents own their machine with 32.7% of them engaged in log merchandize. The average age on chainsaw milling was 15years and it was a means of livelihood for only about 64.4% of the total respondents. This group of respondents is often engaged throughout the year , worked at both open field and forest reverves in Oyo , Osun and Ogun States. The criteria for service charge includes activities. Log girth, location and environment. MA suitable for use with the described T-S-PSE for milling 500mm maximum log diameter was developed at the cost of four thousand nine hundred naira (N 4900). The study was able to develop MA compatible with T-S-PSE and with 69% performance efficiency.